PENGEMBANGAN KEWIRAUSAHAAN ALUMNI JURUSAN GIZI MELALUI PELATIHAN PERIZINAN USAHA - Hastuti, Widi; Moviana, Yenny; Saleky, Yohannes Willihelm; Aeni, Muna Nur (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2024)
Graduates of a university are expected not only to be able to work for an institution or company but also to be able to create jobs for themselves and others. Graduates are expected to have an entrepreneurial spirit and spirit so that they will become graduates who are creative, characterful, capable, and competitive. Universities face challenges in preparing and equipping human resources and graduates with the right competencies and skills in order to continue to be able to contribute to the economic growth and welfare of the Indonesian nation. This community service activity aimed to develop the entrepreneurship of alumni of the Nutrition Department of the Ministry of Health of Bandung. The implementation of business licensing training was carried out for as many as 10 alumni of the Department of Nutrition at the Directorate of Polytechnics of the Ministry of Health Bandung in April 2023. As a result of this activity, there were 10 alumni who have entrepreneurs in the catering, culinary, food, and beverage sectors and as many as 8 people already have Business Identification Numbers (BIN). Halal certification is still being submitted.